KERASULAN PAULUS DALAM TEKS ROMA 1:1-7 DAN REFLEKSI TEOLOGISNYA UNTUK KERASULAN GEREJA MASA KINI - Bauk, Yakobus Adrianus Atolan; Senda, Siprianus Soleman (STIPAS Keuskupan Agung Kupang, 2023)
The apostolic task of preaching the gospel is God's own call and choice. Paul realized this and admitted that his choice as an apostle was not his efforts and merits, but was God's loving kindness. Therefore, in carrying out his apostolic duties, Paul truly carried them out with the spirituality of a servant of Jesus Christ. This research aims to describe Paul's apostleship in Romans 1:1-7. Researchers use text studies and literature studies as research methodologies. This article explains the explanation of Paul who was called, singled out and given the position of apostle, as well as how Paul carried out his apostleship. The final result of this research is that the author presents his theological ideas and reflections as an entry point for the Church to live its apostolate today.